The Six Sigma way : how GE, Motorola, and other top companies are honing their performance - Pande, Peter S. (McGraw-Hill, 2000)
" ... Six Sigma is the organizational quality system that has helped the world's leading companies save millions of dollars, and keep their customers satisfied"--Jacket